Creative innovation takes a (team teaching) family - Pope-Ruark, Rebecca; Motley, Phillip; Moner, William (Teaching and Learning Inquiry, 2019)
Team teaching can be a valuable means of enabling cross-disciplinary collaboration, interdisciplinary study, and pedagogical innovation, but the logistical and intellectual challenges can seem too daunting to overcome. In this essay, we share the story of how four faculty members from professional writing, communications, and computing sciences developed a team teaching “family” as we imagined, created, launched, and ran an innovative experiential learning program at our university. The Design Thinking Studio in Social Innovation is a semester-long program worth four full courses of credit which brought us together with 14 intrepid students from across the university to learn and apply design thinking, Scrum project management, and social innovation theories to a large-scale civic engagement project. Here we explore the faculty lived experience during the pilot semester and how our teach teaching family was crucial to our personal and professional success in this high-stress environment. We then offer tips for creating your own team teaching “family.”